Comparison of sevoflurane and propofol for laryngeal mask airway insertion and pressor response in patients undergoing gynecological procedures - Chavan, Shirishkumar Gulabrao (J Anaesthesiol Clin Pharmacol, 2017)
BACKGROUND AND AIMS: A popular method of providing anesthesia for laryngeal mask airway (LMA) insertion is with the use of propofol. However, bolus propofol has been associated with adverse effects such as hypotension, apnea and pain on injection. Hence, time is needed to search an alternative. We aimed to compare the induction characteristics, ease of LMA insertion, hemodynamic changes and complications with inhalation of 8% sevoflurane vital capacity breath and propofol. MATERIAL AND METHODS: A prospective randomized study of 60 American Society of Anesthesiologists' Grade I and II patients was conducted and distributed among two groups with 30 each undergoing gynecological procedures under general anesthesia. Group P received the injection propofol and Group S received sevoflurane. At the end point of induction, the LMA insertion was attempted. Scoring systems were used to grade the conditions for insertion of the LMA. Induction, LMA insertion characteristics, hemodynamic changes, complications were assessed. Data were recorded and analyzed. Comparison among the study groups was done with unpaired t-test, Mann–Whitney test and Chi-square test. RESULTS: Sevoflurane took a longer time for induction and for LMA insertion than propofol. There was no statistically significant difference between the two groups, with respect to LMA insertion characteristics, heart rate, mean arterial pressure. It is concluded that sevoflurane is associated with good hemodynamic stability and may prove useful incases where propofol is to be avoided. However, the ease of insertion provided with propofol is better.